The power of the ornament: from decorative to ornamental (Palíndromo, 2020)
This article begins with the definitions of the term ornament proposed by Oleg Grabar and Jean-Claude Bonne to expand them in an etymological analysis in order to observe the functional potential of the ornament. The terminological distinctions point to a divergence between a formal and a functional sense, a divergence which is not strictly maintained, but becomes a dialogical differentiation.
Keywords: Ornament; Ornamental; Ornamentum; Kosmos